Cardiac troponin elevations in marathon runners. Role of coronary atherosclerosis and skeletal muscle injury. The MaraCat Study - Paana T.; Jaakkola S.; Bamberg K.; Saraste A.; Tuunainen E.; Wittfooth S.; Kallio P.; Heinonen O.J.; Knuuti J.; Pettersson K.; Airaksinen K.E.J. (ELSEVIER IRELAND LTD, 2022)
Background: Marathon running is associated with transient risk of sudden cardiac death and high cardiac troponin levels are common after race. There is limited data whether coronary atherosclerosis or skeletal muscle injury are related to troponin release caused by strenuous exercise. We aimed to assess whether coronary artery calcification (CAC), plaque vulnerability or skeletal muscle injury relate to cardiac troponin T (cTnT) elevations after marathon race.
Methods: In this observational study, 40 male runners participating in Paavo Nurmi 2018 Marathon were recruited with an open email invitation to evaluate the prevalence of post-race cTnT elevations and their predictors. In addition to baseline and post-race laboratory investigations, 28 runners aged >44 years underwent CAC measurement with computed tomography. Coronary plaque vulnerability was evaluated by free pregnancy associated plasma protein A (fPAPP-A) concentration and skeletal muscle injury by skeletal troponin I (skTnI) measurement.
Results: The post-marathon cTnT concentrations rose above the normal reference limit in 38 (95%) participants. A 10-fold increase in skTnI concentrations was observed and elevated post-race values were seen in all participants. The correlation between the post-race cTnT and post-race skTnI (r(s) = -0.26, p = 0.11) was nonsignificant. CAC was detected (Agatston score > 0) in 15 (53.6%) participants, with a median score of 2.0 (inter-quartile range [IQR] 80). There was no correlation between cTnT with CAC score or post-race fPAPP-A levels.
Conclusions: Asymptomatic cardiac troponin elevations are common after prolonged strenuous exercise, but are not related to markers of coronary atherosclerosis, plaque vulnerability or skeletal muscle injury. (C) 2019 The Authors. Published by Elsevier B.V.